Metabolomics and Microbiomics Reveal Impacts of Rhizosphere Metabolites on Alfalfa Continuous Cropping - Wang, Ruiting; Liu, Jinxin; Jiang, Wanyi; Ji, Pingsheng; Li, Yonggang (Frontiers in Microbiology, 2022)
Alfalfa long-term continuous cropping (CC) can pose a serious threat to alfalfa production. However, the mechanism of alfalfa CC obstacle is unclear as of today. In this study, we determined physic-chemical property, microbial population structure, and metabolite differences of alfalfa rhizosphere soils with CC for 1, 7, and 14-years based on analysis of metabolomics and microbiomics. Shifts of functional microorganisms in rhizosphere soil were analyzed, key metabolites and their effects on alfalfa seeds, seedlings and root rot pathogens were assessed.The main factors of CC obstacle were not the lack of nutrients or water in alfalfa rhizosphere soils. Based on metabolomics and microbiomics analysis, the effects of the two key metabolites in alfalfa rhizosphere soils, p-coumaric acid and ferulic acid, on alfalfa seed and seedling growth and root rot pathogens were basically consistent with the influence of CC obstacles in the field. With the increase of CC years, the microbial community in soils changed from fungal to bacterial, and beneficial microorganisms decreased with the increase of CC years, which echoed the performance of alfalfa CC obstacles. Among the key metabolites, the autotoxicity of p-coumaric acid was the strongest.This study fully proved that the continuous accumulation of autotoxic substances in alfalfa rhizosphere was the key factor causing alfalfa CC obstacles.